Fire Resistance Parameters for Glazed Non-Load-Bearing Curtain Walling Structures. Extended Application. (2015) - Gravit, Marina; Gumenyuk, Vasiliy; Nedryshkin, Oleg
Abstract: This article provides a development of the new state standard of the Russian Federation 55988-2014 "Building structures. Extended application of results from fire resistance tests for glazed non-loadbearing curtain walling structures". This standard is harmonized with the current European standard EN 15254-4: 2008 + A1: 2011 "Extended application of results from fire resistance tests – Non-loadbearing walls Part 4: Glazed constructions" and modified (not made identical) in relation to it, as there are significant differences in Russia and Europe concerning the systems of rationing the fire resistance of non-loadbearing glazed walls.